ВІДНОВЛЮВАНІ ДЖЕРЕЛА В СИСТЕМАХ ЕНЕРГОПОСТАЧАННЯ МІСТ УКРАЇНИ - Карп, І.М.; Нікітін, Є.Є.; П’яних, К.Є. (Інститут електродинаміки НАН України, Київ, 2021)
70% of the population of Ukraine lives in cities. Electric energy supply of cities with dense buildings is provided mainly from centralized generation sources: TPPs, CHPs, NPPs, RES, and heat energy - from CHPs and gas boilers. Possibilities of energy self-sufficiency of Ukrainian cities based on use of alternative and local energy sources are analyzed. There is a global trend of increasing share of RES in cities energy supply, especially in cities and districts with cottage development. Providing cities with their own energy resources can be achieved through integrated use of renewable and local sources. Production of electricity from renewable sources in terms of return on investment EROI and normalized energy cost over life cycle of LCOE generation source is close to traditional sources indicators. Examples of RES usage to meet energy needs of houses and settlements in Europe are given. High cost of renewable energy stimulates development of this area in Ukraine. Efficiency of renewable and local sources usage in buildings is achieved only with simultaneous introduction of energy saving measures - insulation of buildings, introduction of energy control systems. References 14.